Influence of Carrot Pulp Fortified with Different Concentrations of Apple Pulp on Blended Jam - Ahmed, Ishfaq; Ullah, Shermat; Khan, Arsalan; Ayub, Muhammad; Shamrez, Baber; Khan, Mati Ullah (Biological Sciences - PJSIR, 2017)
The aim of this study was to evaluate various combination and effect of storage period on the quality of carrot apple blended jam at ambient temperature (18-25 °C). The treatments were CA0, CA1, CA2, CA3, CA4 and CA5. All the treatments were examined for physicochemical properties i.e., total soluble solids (TSS), pH, reducing sugars (%), percent acidity, non-reducing sugars (%), ascorbic acid (mg/100 g), as well as for sensory properties at fifteen days interval for a total storage period of 90 days. Significant increase (P<0.05) were examined in TSS (67.45-70.40 °brix), acidity (0.64-0.80) and reducing sugars (16.64-27.78). While, significant decrease (P<0.05) were examined in pH (3.63-3.44), non reducing sugars (45.04-27.69), ascorbic acid (7.81-5.52 mg/100 g), colour (7.33-4.35), taste (7.40-4.12), texture (7.22- 4.06) and overall acceptability (7.36-4.14). Statistical results concluded that treatment and storage has a significant effect on the quality and stability of carrot pulp and apple pulp blend jam. Results revealed that good quality jam could be prepared with equal amount of carrot and apple pulp, which showed with minimum damage to physiochemical and sensory attributes among the other treatment even after 90 days of storage.